2018
DOI: 10.1111/1750-3841.14278
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Effective Moisture Diffusivity in Corn Tortilla Baking

Abstract: The analytical solutions of the Fick's law of diffusion for the moisture content in products that can be represented as an infinite plate, considering variable diffusivity, can be useful in studies when accurate estimations of effective diffusivity and concentration are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Iribe‐Salazar et al . (2018) reported that in corn tortilla chips, baking time and temperature had an important effect on moisture content. The authors applied a modelling process after varying baking times (0, 120, 240, 360, 480, and 630 s) and baking temperature (180 and 270 °C) to predict the dispersion in moisture content throughout the baking process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iribe‐Salazar et al . (2018) reported that in corn tortilla chips, baking time and temperature had an important effect on moisture content. The authors applied a modelling process after varying baking times (0, 120, 240, 360, 480, and 630 s) and baking temperature (180 and 270 °C) to predict the dispersion in moisture content throughout the baking process.…”
Section: Resultsmentioning
confidence: 99%
“…Quick vaporisation and diffusion of moisture occurs through the pores in the chips, reducing moisture content and a w . Iribe- Salazar et al (2018) reported that in corn tortilla chips, baking time and temperature had an important effect on moisture content. The authors applied a modelling process after varying baking times (0, 120, 240, 360, 480, and 630 s) and baking temperature (180 and 270 °C) to International Journal of Food Science and Technology 2024 predict the dispersion in moisture content throughout the baking process.…”
Section: Moisture Content and A W Of The Tortilla Chipsmentioning
confidence: 99%
“…The dough was prepared as mentioned above. The baking procedure has made some modification (Iribe- Salazar et al, 2018). The corn tortilla was continued to be placed and baked in a preheated electric oven at 225 °C for 5 min.…”
Section: Bakingmentioning
confidence: 99%
“…Pan cooking for domestic heat processing of flour cereal products has not been traditionally as widely studied as oven baking in terms of heat and mass transfer (Kokolj et al, 2017;Zhang et al, 2017;Iribe-Salazar et al, 2018). Current models are unable to adequately predict the influence of batter composition on transfer phenomena.…”
Section: Introductionmentioning
confidence: 99%